Membentuk usahawan muslim: Peranan dana masjid - Borhan, J.T.; Mohd Hussin, M.Y.; Muhammad, F.; Abu, M.F. (2011)
Capital is very crucial in the formation and establishment of business activities especially for entrepreneurs who newly venture into the business world. Currently, banking and financial institutions play significant roles in fulfilling the need of these entrepreneurs. However, for new entrepreneurs, the failure to meet the requirements needed by financing institution causes their ideas, innovation, creativity and efforts to be undelivered. Therefore, the problem of entrepreneur dependency on banking institutions can be resolved by the establishment of the mosque fund. Through this fund, the process of producing Muslim entrepreneur can be realized and henceforth it will impact positively to the local development in the future.